can help me with this one??
1. Use the remainder theorm to find the remainder when 2x^2-3x^2+7x-4
is divided by (x+1)
thanks guys..
Did you REALLY mean $\displaystyle 2x^2-3x^2+7x-4$ or what it supposed to be:
$\displaystyle 2x^3-3x^2+7x-4$
I'm assuming the last.
Let $\displaystyle P(x) = 2x^3-3x^2+7x-4$
We can express this in the form:
$\displaystyle P(x) = q(x)(x+1) + r(x) $
$\displaystyle r(x)$ is the remainder!
Consider $\displaystyle P(-1) $
$\displaystyle P(-1) = q(-1)(-1+1) + r(-1) $
$\displaystyle P(-1) = q(-1)(0) + r(-1) $
$\displaystyle P(-1) = r(-1) $
And we can find P(-1) from the original equation!:
$\displaystyle P(-1) = 2(-1)^3-3(-1)^2+7(-1)-4$